Carnegie's maid ebook A novel. - Benedict, Marie (2018)
The USA Today Bestseller From the bestselling author of The Only Woman in the Room comes a mesmerizing tale of historical fiction that asks what kind of woman could have inspired an American dynasty. Clara Kelley is not who they think she is. She's not the experienced Irish maid who was hired to work in one of Pittsburgh's grandest households. She's a poor farmer's daughter with nowhere to go and nothing in her pockets. But the woman who shares her name has vanished, and assuming her identity just might get Clara some money to send back home. Clara must rely on resolve as strong as the steel Pittsburgh is becoming famous for and an uncanny understanding of business, attributes that quickly gain her Carnegie's trust. But she still can't let her guard down, not even when Andrew becomes something more than an employer. Revealing her past might ruin her future—and her family's. With captivating insight and heart, Carnegie's Maid is a book of fascinating 19th century historical fiction. Discover the story of one brilliant woman who may have spurred Andrew Carnegie's transformation from ruthless industrialist to the world's first true philanthropist. Other Bestselling Historical Fiction from Marie Benedict: The Mystery of Mrs. Christie Lady Clementine The Only Woman in the Room The Other Einstein